Penerapan Model Pembelajaran Discovery Untuk Meningkatkan Keterampilan Komunikasi Siswa - Nirwanasari Nur Khayani; Ari Winarti (LAMBDA : Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2023)
This research is a classroom action research that aims to improve students communication skills through the application of the Discovery Learnig model. This research was conducted in class VIII A of SMP Negeri 10 Yogyakarta in the odd semester of the 2023/2024 academic year with a total of 34 students. This research was conducted in two cycles. Data collection was carried out using observation and learning achievement tests. The data collected was analyzed using descriptive statistical analysis, where the indicator of the success of this study was an increase in the average value of mastery of communication skills during learning in each cycle. The results showed that in cycle I, an average score of 40 was obtained for 40 students with the criteria of being less skilled at communicating, as many as 27 students getting an average score of 56 with the criterion of being sufficiently skilled at communicating, and as many as 4 students getting an average score of 62 with the criteria for being skilled communicate. Cycle II experienced an increase with a communication skills score of 87 for 29 students with very skilled communication criteria, and as many as 5 students got a score of 77 with communication skills criteria. Thus it can be concluded that the use of Discovery Learning model can improve students communication skills which have an impact on increasing student learning outcomes.